2012
DOI: 10.1093/infdis/jis378
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Variation in CD55 Increases the Severity of 2009 Pandemic H1N1 Influenza A Virus Infection

Abstract: Infection due to 2009 pandemic H1N1 influenza A virus (A[H1N1]pdm09) is commonly manifested as mild infection but occasionally as severe pneumonia. We hypothesized that host genetic variations may contribute to disease severity. An initially small-scale genome-wide association study guided the selection of CD55 single-nucleotide polymorphisms in 425 Chinese patients with severe (n = 177) or mild (n = 248) disease. Carriers of rs2564978 genotype T/T were significantly associated with severe infection (odds rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 35 publications
2
78
2
4
Order By: Relevance
“…DAF rs2564978 T > C polymorphism is located in the promoter of DAF. Evidences have demonstrated that the carriers with DAF rs2564978 C allele exhibited significantly higher DAF mRNA expression levels on moncytes that those with TT genotype (Zhou et al, 2012). In our present study, we genotyped the DAF rs2564978 polymorphism among our case-control population and found that CC genotype carriers had marginally significant association with gastric cancer risk compared with TT genotype carriers with OR (95% CI) of 1.42(0.99-2.05) (P = 0.058).…”
Section: Discussionmentioning
confidence: 99%
“…DAF rs2564978 T > C polymorphism is located in the promoter of DAF. Evidences have demonstrated that the carriers with DAF rs2564978 C allele exhibited significantly higher DAF mRNA expression levels on moncytes that those with TT genotype (Zhou et al, 2012). In our present study, we genotyped the DAF rs2564978 polymorphism among our case-control population and found that CC genotype carriers had marginally significant association with gastric cancer risk compared with TT genotype carriers with OR (95% CI) of 1.42(0.99-2.05) (P = 0.058).…”
Section: Discussionmentioning
confidence: 99%
“…A SNP in CD55 , rs2564978, was chosen from 5,166 SNPs identified by a small-scale GWAS study in 25 Chinese patients with severe influenza and 26 controls [106]. This SNP caused reduced expression of CD55 (also known as decay accelerating factor, DAF), which can reduce epithelial cell damage during influenza infection [106]. A similar GWAS study of 42 Chinese patients with severe pH1N1 or H7N9 infection and 42 controls crossed with a quantitative cis-QTL study in the lung yielded 1,114 SNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Several potential genetic determinants associated with A(H1N1)pdm09 infection have been described, including TNF (Antonopoulou et al, 2012), IFN-inducible transmembrane (Everitt et al, 2012), killer-cell immunoglobulin-like receptor (Aranda-Romo et al, 2012), complement regulatory protein CD55 (Zhou et al, 2012) and Toll-like receptor 3 (Esposito et al, 2012). Data relating to the role of chemokine receptor 5 (CCR5) in severe A(H1N1)pdm09-infected patients are contradictory and have been debated (Keynan et al, 2010;Rodriguez et al, 2013;Sironi et al, 2014).…”
mentioning
confidence: 99%